Novel heterostructured metal doped MgFe2O4@g-C3N4 nanocomposites with superior photo-Fenton preformance for antibiotics removal: One-step synthesis and synergistic mechanism. (1st November 2022) - Qiu, Shuxing; Gou, Lizheng; Cheng, Fangqin; Zhang, Mei; Guo, Min
Abstract: A novel metal doped MgFe2 O4 @g-C3 N4 (m-MF@CN) nanocomposite was synthesized by one-pot method using saprolite laterite nickel ore and urea as raw materials. The heterostructure was verified as an effective heterogeneous Fenton-like catalyst for degrading antibiotics including tetracycline, oxytetracycline and chlortetracycline hydrochloride, and the related catalytic mechanism was elaborated in detail. Under the optimum conditions, the m-MF@CN/H2 O2 / vis system exhibited superior photo-Fenton property (degradation efficiency of 93.15% within 30 min, TOC removal efficiency was as high as 60.54% within 120 min) and cycle stability for tetracycline removal. The combination of MgFe2 O4 and g-C3 N4 enhanced the absorption of visible light, and the energy level matched heterojunction promoted the separation of photogenerated electron-holes to accelerate the redox cycle of ≡Fe 3+ /≡Fe 2+ . Free radical quenching and electron spin resonance (ESR) analysis confirmed that O2 − was the main active species, h + and OH also played a synergistic role in the degrading reactions. Notably, a possible degradation pathway of tetracycline was proposed according to the intermediates produced in the reaction process. The one-step synthesized m-MF@CN nanocomposite catalysts possessed high catalytic performance, good stability and recoverability, which not only realized the high-value utilization of ore raw materials, but also provided a potential practical way for efficient treatment of antibiotic wastewater. Graphical abstract: Image 1 Highlights: Metal-doped MgFe2 O4 @g-C3 N4 nanocomposite was synthesized by one-pot method. Energy level matched heterostructure promoted photogenerated carriers separation. Composites presented high catalytic performance, stability and recoverability. The related degrading mechanism and pathway of tetracycline were revealed. A potential way was provided for efficient treatment of antibiotic wastewater.